Development of an Information Search Strategies Curriculum for Secondary School Students and Evaluation of Its Effect - Şerefoğlu Henkoğlu, Halise; Mahiroğlu, Ahmet (Information World, 2016)
The purpose of this study is to develop a curriculum that aims to teach secondary school students’ online information searching skills, and to evaluate the effectiveness of the curriculum on improving the students’ online information searching strategies. In the study, “Curriculum for the Information Searching Strategies on the Internet” was developed in order to teach secondary school students online information searching strategies and support them to develop their knowledge and skills of how to search information online effectively. Upon developing the curriculum; an instruction was given to a total of 98 secondary school students, who are the fifth, sixth and seventh graders of a secondary school. In order to investigate the effect of the instruction on the students’ online information searching strategies; data was collected through pre and post questionnaires as in the form of the data collection instrument, “Secondary School Students’ Information Search Strategies on the Internet Questionnaire” which was developed by the researchers. Pre and post assessments required the students express the strategies they used while searching information on the internet before and after the instruction consecutively. Statistical analyses including dependent samples t-test and Wilcoxon signed rank test were employed in order to test the effect of the instruction on students’ online information searching strategies. Results suggest that instruction in the developed curriculum improves the secondary school students’ online information searching skills.
Keywords: information search; secondary school students; curriculum; internet; web; strategy